MENINGKATKAN PARTISIPASI SISWA DALAM AKTIVITAS FISIK PADA MATA PELAJARAN PJOK MELALUI METODE PEMBELAJARAN YANG INOVATIF DI KELAS VI SDN JAGALAN 1 KOTA KEDIRI - Roviyan Yusuf Eka Wicaksana; Irwan Setiawan; Andri Prasetyo Sagitarius (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Student participation in PJOK learning tends to decline due to monotonous teaching methods. This study aims to increase student participation through the implementation of game-based methods. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles at SDN Jagalan 1, Kediri City, with 28 sixth-grade students as the sample. Data were collected through observation, documentation, and questionnaires, then analyzed using the percentage method. The results show that in the first cycle, 66.43% of students responded positively to the applied teaching method, while in the second cycle, this figure significantly increased to 94.31% after implementing game-based innovations. Additionally, three key aspects—motivation for exercise, interest in learning, and enjoyment in games—achieved the maximum percentage (100%). This improvement demonstrates that game-based methods effectively enhance motivation, engagement, and the quality of PJOK learning. Therefore, implementing game-based methods can be an innovative strategy to increase student participation in physical activities.